Loose nanofiltration membrane as well as preparation method and application thereof

By using interfacial polymerization to form a functional layer on a PAN fiber-based membrane, and by using weakly reactive aqueous monomers and crosslinking agents to regulate the membrane structure, the problem of balancing flux and selectivity in loose nanofiltration membranes was solved, achieving efficient separation of dyes and salts.

CN120860846APending Publication Date: 2025-10-31PINGDINGSHAN IND TECHNOLOGY RESEARCH INSTITUTE OF HENAN ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511130089.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing loose nanofiltration membranes have uncontrollable pore size during the construction process, making it difficult to achieve both high flux and high selectivity. Furthermore, the interfacial polymerization process is sensitive to operating conditions, affecting separation performance and stability.

Method used

Using PAN fiber-based membrane as the substrate, a functional layer is formed on it through interfacial polymerization. Weakly reactive aqueous monomers such as polyethyleneimine and piperazine-2-carboxylic acid are used in combination with trimesoyl chloride to regulate the membrane structure and crosslinking degree, thus forming a loose nanofiltration membrane.

Benefits of technology

It achieves high dye rejection and low salt rejection under high throughput conditions, has good membrane pore size stability, and is suitable for efficient separation of dyes and inorganic salts, especially for the separation of negatively charged dyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120860846A_ABST
    Figure CN120860846A_ABST
Patent Text Reader

Abstract

The invention provides a loose nanofiltration membrane and a preparation method and application thereof.The loose nanofiltration membrane comprises a PAN fiber base membrane and a functional layer attached to the PAN fiber base membrane, and raw materials of the functional layer comprise a first water-phase raw material, a second water-phase raw material and an organic-phase raw material; the first water phase raw material is selected from any one or two of polyethyleneimine and ethylenediamine, the second water phase raw material is selected from any one or more of piperazine-2-carboxylic acid, 2, 3-piperazine dicarboxylic acid, 1-methylsulfonyl piperazine, 2-cyano piperazine and N-acetyl piperazine, and the third water phase raw material is selected from any one or more of piperazine-2-carboxylic acid, 2, 3-piperazinedicarboxylic acid, 1-methylsulfonyl piperazine, 2-cyano piperazine and N-acetyl piperazine. The organic phase raw material is selected from any one or more of trimesoyl chloride, terephthaloyl chloride and isophthaloyl chloride. The loose nanofiltration membrane disclosed by the invention has relatively high permeation flux and excellent dye interception capability on various dyes, has excellent structural stability, and shows huge application potential in an actual dye wastewater separation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane separation technology, and in particular to a loose nanofiltration membrane, its preparation method, and its uses. Background Technology

[0002] In dye wastewater treatment, achieving efficient separation of salts and dyes is a key technological step in promoting the resource utilization of wastewater. The dyeing and printing industry often adds large amounts of inorganic salts (such as sodium sulfate and sodium chloride) to promote dye uptake, resulting in wastewater containing high concentrations of dyes and inorganic salt components. If this mixed wastewater is discharged directly without effective treatment, it will not only exacerbate water pollution but may also adversely affect subsequent biological treatment systems. Effective separation of salts and dyes not only facilitates the recovery and reuse of inorganic salts and reduces wastewater treatment costs but also provides favorable conditions for the concentration and reuse of dyes or subsequent advanced treatment. Therefore, developing efficient and feasible salt-dye separation technologies has significant engineering application value for achieving the reduction and resource utilization of dyeing and printing wastewater.

[0003] Currently, membrane separation technology has become a research hotspot in the field of salt and dye separation due to its low energy consumption, simple operation, and high separation efficiency. Among them, loose nanofiltration membranes, with their high rejection rate for dye molecules and good permeability to small molecule inorganic salts, are particularly suitable for the treatment of high-salt, high-color wastewater. Among numerous membrane preparation technologies, interfacial polymerization is widely used in nanofiltration membrane construction due to its advantages such as process controllability, dense and uniform membrane layers, and easily adjustable separation performance. By adjusting the type, concentration, and reaction conditions of the interfacial polymerization monomers, the pore size and surface chemical properties of the membrane layer can be effectively controlled, thereby achieving selective separation of dyes and salts.

[0004] Although interfacial polymerization technology has been widely used in nanofiltration membrane preparation, and membrane structure can be adjusted by controlling reaction conditions, certain limitations remain in constructing loose nanofiltration membranes suitable for efficient salt and dye separation. On the one hand, traditional interfacial polymerization, such as the reaction of polyethyleneimine (PEI) and trimesoyl chloride (TMC) to produce polyamide nanofiltration membranes, tends to form dense membrane layers due to the excessively rapid reactivity of the amine monomers, making it difficult to control the interfacial process and limiting water flux, thus making it difficult to achieve both high flux and high selectivity. On the other hand, when attempting to construct loosely structured membrane layers, using monomers with low reactivity can improve membrane permeability to some extent, but it may result in a polyamide layer with too low crosslinking degree, which can easily lead to a decrease in dye rejection rate and cause an imbalance in separation performance. In addition, the interfacial polymerization process is highly sensitive to operating conditions; factors such as monomer diffusion rate, solvent system, and reaction time can significantly affect the uniformity and stability of the membrane structure, thereby affecting separation performance and long-term operating results. Therefore, it is urgent to explore interfacial polymerization optimization strategies with controllable structure and balanced performance to achieve efficient synergistic separation of salt and dye. Summary of the Invention

[0005] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a loose nanofiltration membrane, its preparation method and uses, to solve the problem that the membrane pore size is uncontrollable in the prior art and cannot achieve both high flux and high selectivity.

[0006] To achieve the above and other related objectives, the present invention provides a loose nanofiltration membrane, its preparation method, and its uses.

[0007] The first aspect of the present invention provides a loose nanofiltration membrane, the loose nanofiltration membrane comprising a PAN fiber base membrane and a functional layer attached to the PAN fiber base membrane, wherein the raw materials of the functional layer comprise a first aqueous phase raw material, a second aqueous phase raw material, and an organic phase raw material; the first aqueous phase raw material is selected from any one or two of polyethyleneimine and ethylenediamine; the second aqueous phase raw material is selected from any one or more of piperazine-2-carboxylic acid, 2,3-piperazine dicarboxylic acid, 1-methanesulfonylpiperazine, 2-cyanopiperazine, and N-acetylpiperazine; and the organic phase raw material is selected from any one or more of trimesoyl chloride, terephthaloyl chloride, and isophthaloyl chloride.

[0008] Preferably, the first aqueous phase raw material is polyethyleneimine.

[0009] Preferably, the second aqueous phase raw material is piperazine-2-carboxylic acid.

[0010] Preferably, the organic phase raw material is pyromellitic acid chloride.

[0011] Preferably, the number-average molecular weight of the PAN used in the PAN fiber base film is 100-200K.

[0012] More preferably, the number-average molecular weight of the PAN used in the PAN fiber base film is 120-180K; including but not limited to 120K, 130K, 140K, 150K, 160K, 170K or 180K.

[0013] Preferably, the weight-average molecular weight of the polyethyleneimine is 500–1000 Da.

[0014] More preferably, the weight-average molecular weight of the polyethyleneimine is 500 to 800 Da; including but not limited to 500 Da, 550 Da, 600 Da, 650 Da, 700 Da, 750 Da or 800 Da.

[0015] Preferably, the mass ratio of the first aqueous phase raw material, the second aqueous phase raw material, and the organic phase raw material is 1:(0.2-5):(0.2-10).

[0016] More preferably, the mass ratio of the first aqueous phase raw material, the second aqueous phase raw material, and the organic phase raw material is 1:(0.3-3):(0.5-5).

[0017] More preferably, the mass ratio of the first aqueous phase raw material, the second aqueous phase raw material, and the organic phase raw material is 1:(0.5~2):(0.5~3); for example, it can be 1:0.5:0.5, 1:1:0.5, 1:2:0.5, 1:0.5:1, 1:1:1, 1:2:1, 1:0.5:2, 1:1:2, 1:2:2, 1:0.5:3, 1:1:3, or 1:2:3.

[0018] Preferably, the functional layer is formed by sequentially immersing the PAN fiber base membrane in an aqueous raw material dispersion and an organic raw material dispersion; the aqueous raw material dispersion includes the following characteristics:

[0019] a) The concentration of the first aqueous phase feedstock is 0.01 wt% to 0.1 wt%;

[0020] b) The concentration of the second aqueous phase feedstock is 0.01 wt% to 0.1 wt%;

[0021] c) The solvent in the aqueous raw material dispersion is water;

[0022] The organic phase raw material dispersion includes the following characteristics:

[0023] a) The concentration of the organic phase raw material is 0.01 wt% to 0.1 wt%;

[0024] b) The solvent in the organic phase raw material dispersion is selected from any one or two of n-hexane and cyclohexane.

[0025] More preferably, the concentration of the first aqueous raw material is 0.01wt% to 0.05wt%.

[0026] More preferably, the concentration of the first aqueous raw material is 0.02wt% to 0.04wt%.

[0027] More preferably, the concentration of the first aqueous raw material is 0.02wt% to 0.03wt%; for example, it can be 0.02wt%, 0.021wt%, 0.022wt%, 0.023wt%, 0.024wt%, 0.025wt%, 0.026wt%, 0.027wt%, 0.028wt%, 0.029wt%, or 0.03wt%.

[0028] Most preferably, the concentration of the first aqueous raw material is 0.021 wt% to 0.029 wt%.

[0029] More preferably, the concentration of the second aqueous phase raw material is 0.01wt% to 0.05wt%.

[0030] More preferably, the concentration of the second aqueous phase raw material is 0.01wt% to 0.03wt%.

[0031] More preferably, the concentration of the second aqueous raw material is 0.01 wt% to 0.03 wt%; for example, it can be 0.02 wt%, 0.021 wt%, 0.022 wt%, 0.023 wt%, 0.024 wt%, 0.025 wt%, 0.026 wt%, 0.027 wt%, 0.028 wt%, 0.029 wt%, or 0.03 wt%.

[0032] Most preferably, the concentration of the second aqueous phase raw material is 0.021 wt% to 0.029 wt%.

[0033] More preferably, the concentration of the organic phase raw material is 0.02wt% to 0.08wt%; for example, it can be 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, or 0.08wt%.

[0034] Preferably, the thickness of the loose nanofiltration membrane is 40-50 μm; including but not limited to 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm or 50 μm.

[0035] Preferably, the thickness of the functional layer in the loose nanofiltration membrane is 30–50 nm.

[0036] Preferably, the water contact angle of the loose nanofiltration membrane is ≤70°.

[0037] More preferably, the water contact angle of the loose nanofiltration membrane is 30° to 70°.

[0038] More preferably, the water contact angle of the loose nanofiltration membrane is 45° to 70°; for example, it can be 45°, 50°, 55°, 60°, 65° or 70°.

[0039] Preferably, the pore size of the loose nanofiltration membrane is 0.2 to 2 nm.

[0040] More preferably, the pore size of the loose nanofiltration membrane is 0.2 to 1.8 nm; for example, it can be 0.2 nm, 0.4 nm, 0.6 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.4 nm, 1.6 nm or 1.8 nm.

[0041] Preferably, the average effective pore radius (μm) of the loose nanofiltration membranep The wavelength range is 0.7–0.8 nm; for example, it can be 0.7 nm, 0.71 nm, 0.72 nm, 0.73 nm, 0.74 nm, 0.75 nm, 0.76 nm, 0.77 nm, 0.78 nm, 0.79 nm or 0.8 nm.

[0042] Preferably, the geometric standard deviation (σ) of the pore size of the loose nanofiltration membrane is... p <1.5.

[0043] More preferably, the geometric standard deviation (σ) of the pore size of the loose nanofiltration membrane p <1.3.

[0044] Preferably, the loose nanofiltration membrane has a Zeta potential of <0 in a KCl electrolyte solution with a pH of 3 to 10.

[0045] More preferably, the loose nanofiltration membrane has a Zeta potential ≤ -5 in a KCl electrolyte solution with a pH of 3–10.

[0046] More preferably, the loose nanofiltration membrane has a Zeta potential of -35 to -5 in a KCl electrolyte solution with a pH of 3 to 10.

[0047] Preferably, the loose nanofiltration membrane exhibits a Congo red rejection rate >98% and a solution flux ≥28 L / m³ in a 100 ppm Congo red aqueous solution. -2 h -1 bar -1 .

[0048] More preferably, the loose nanofiltration membrane has a rejection rate of >99% for Congo red in a 100 ppm aqueous solution of Congo red.

[0049] More preferably, the loose nanofiltration membrane has a rejection rate of ≥99.5% for Congo red in a 100 ppm aqueous solution.

[0050] More preferably, the porous nanofiltration membrane has a solution flux of 28–80 Lm in a 100 ppm Congo red aqueous solution. -2 h -1 bar -1 For example, it can be 28L m -2 h -1 bar -1 30L m -2 h -1 bar -1 40L m -2 h -1 bar -1 50L m -2 h -1bar -1 60L m -2 h -1 bar -1 70L m -2 h -1 bar -1 Or 80L m -2 h -1 bar -1 .

[0051] Preferably, the loose nanofiltration membrane exhibits a NaCl rejection rate of <20% and a solution flux of >35 L / m³ in a 2000 ppm NaCl aqueous solution. -2 h -1 bar -1 .

[0052] More preferably, the loose nanofiltration membrane has a NaCl rejection rate of 1% to 20% in a 2000 ppm NaCl aqueous solution; for example, it can be 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18% or 20%.

[0053] More preferably, the porous nanofiltration membrane has a solution flux of 36–125 Lm in a 2000 ppm NaCl aqueous solution. -2 h -1 bar -1 For example, it can be 36L m -2 h -1 bar -1 40L m -2 h -1 bar -1 50L m -2 h -1 bar -1 60L m -2 h -1 bar -1 70L m -2 h -1 bar -1 80L m -2 h -1 bar -1 90L m -2 h -1 bar -1 100L m -2 h -1 bar -1 110L m -2 h -1 bar -1 Or. 120L m -2 h -1 bar-1 .

[0054] Preferably, the loose nanofiltration membrane has a salt staining separation factor > 60 in a mixed aqueous solution of Congo red 100 ppm and NaCl 2000 ppm.

[0055] More preferably, the loose nanofiltration membrane has a salt staining separation factor >150 in a mixed aqueous solution of Congo red 100 ppm and NaCl 2000 ppm.

[0056] More preferably, the salt staining separation factor of the loose nanofiltration membrane in a mixed aqueous solution of Congo red 100 ppm and NaCl 2000 ppm is 190 to 290; for example, it can be 190, 200, 210, 220, 230, 240, 250, 260, 270, 280 or 290.

[0057] Preferably, the loose nanofiltration membrane has a molecular weight cutoff of 530–545 Da.

[0058] More preferably, the loose nanofiltration membrane has a molecular weight cutoff of 535–545 Da.

[0059] The molecular weight cutoff of the loose nanofiltration membrane mentioned above is the molecular weight of the substance when the membrane achieves a 90% retention rate.

[0060] The second aspect of the present invention provides a method for preparing a loose nanofiltration membrane, the method comprising: sequentially immersing a PAN fiber base membrane in an aqueous phase containing an aqueous raw material and an organic phase containing an organic raw material, and then crosslinking it by heating to prepare the loose nanofiltration membrane.

[0061] Preferably, the PAN fiber base film is prepared by electrospinning, and the electrospinning solution uses DMF and / or acetone as solvents, with the concentration of PAN in the electrospinning solution being 10-20 wt%.

[0062] More preferably, the concentration of PAN in the spinning solution is 10-15 wt%; including but not limited to 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%.

[0063] More preferably, the electrospinning parameters are any one or more of the following: spinning amount of 3-8 mL, pushing speed of 10-20 μL / min, voltage of 15-25 kV, collection distance of 10-20 cm, spinning temperature of 20-30 °C, and spinning humidity of 30%-50%.

[0064] More preferably, the spinning amount is 3 to 6 mL; for example, it can be 3 mL, 4 mL, 5 mL or 6 mL.

[0065] More preferably, the pushing rate is 15 to 20 μL / min; for example, it can be 15 μL / min, 16 μL / min, 17 μL / min, 18 μL / min, 19 μL / min or 20 μL / min.

[0066] More preferably, the voltage is 18 to 22 kV; for example, it can be 18 kV, 19 kV, 20 kV, 21 kV or 22 kV.

[0067] More preferably, the collection distance is 13 to 18 cm; for example, it can be 13 cm, 14 cm, 15 cm, 16 cm, 17 cm or 18 cm.

[0068] More preferably, the spinning temperature is 23 to 28°C; for example, it can be 23°C, 24°C, 25°C, 26°C, 27°C or 28°C.

[0069] More preferably, the spinning humidity is 35% to 45%; for example, it can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%.

[0070] Preferably, the PAN fiber base is soaked in an aqueous phase containing the aqueous raw material for 1 to 10 minutes.

[0071] More preferably, the PAN fiber base is soaked in an aqueous phase containing the aqueous raw material for 1 to 5 minutes; for example, it can be 1 minute, 2 minutes, 3 minutes, 4 minutes or 5 minutes.

[0072] Preferably, the PAN fiber base is soaked in an organic phase containing organic phase raw materials for 1 to 10 minutes.

[0073] More preferably, the PAN fiber base is soaked in an organic phase containing organic phase raw materials for 1 to 5 minutes; for example, it can be 1 minute, 2 minutes, 3 minutes, 4 minutes or 5 minutes.

[0074] Preferably, the temperature for the heating crosslinking is 60–80°C.

[0075] More preferably, the temperature for heating and crosslinking is 60-70°C; for example, it can be 60°C, 62°C, 64°C, 65°C, 66°C, 68°C or 70°C.

[0076] Preferably, the heating crosslinking time is 10 to 20 minutes; for example, it can be 10 minutes, 12 minutes, 15 minutes, 16 minutes, 18 minutes or 20 minutes.

[0077] A third aspect of the present invention provides the use of the above-described loose nanofiltration membrane for removing hydrophilic macromolecules with a molecular weight ≥550 Da from aqueous solutions.

[0078] The fourth aspect of the present invention provides the use of the above-described loose nanofiltration membrane for removing hydrophilic dyes with a molecular weight ≥550 Da from aqueous solutions.

[0079] More preferably, the molecular weight of the dye is 550 Da to 2000 Da; including but not limited to 550 Da, 600 Da, 800 Da, 1000 Da, 1200 Da, 1500 Da, 1800 Da or 2000 Da.

[0080] More preferably, the molecular weight of the dye is ≥580 Da.

[0081] More preferably, the dye molecule is selected from any one or more of Acid Fuchsin, Congo Red, Direct Red-80, Acid Violet 7, Acid Red 6B, Direct Blue 71, Reactive Black 5, and Reactive Red 195.

[0082] As described above, the loose nanofiltration membrane, its preparation method, and its uses of the present invention have the following beneficial effects:

[0083] 1. The loose nanofiltration membrane prepared by this invention has good hydrophilicity and high dimensional stability. The membrane pore size does not deform within a pressure range of 1-5 bar.

[0084] 2. The loose nanofiltration membrane prepared by this invention has high permeation flux and excellent dye retention capacity for a variety of dyes.

[0085] 3. The loose nanofiltration membrane prepared by this invention has excellent structural stability and can still maintain a high dye rejection capacity during long-term wastewater treatment (with a rejection rate of more than 99% within 14 hours), showing great application potential in actual dye wastewater separation processes. Attached Figure Description

[0086] Figure 1 The diagram shows the preparation process of the loose nanofiltration membrane of the present invention.

[0087] Figure 2 The images shown are surface morphology diagrams of five different loose nanofiltration membranes in Embodiment 2 of the present invention; wherein... Figure 2 a is the surface morphology diagram of M0. Figure 2 b is the surface morphology diagram of M1. Figure 2 c is the surface morphology diagram of M2. Figure 2 d is the surface morphology diagram of M3. Figure 2 e is a surface topography diagram of M4.

[0088] Figure 3The images shown are cross-sectional morphology diagrams of five different loose nanofiltration membranes in Embodiment 2 of the present invention; wherein, Figure 3 a is the cross-sectional topography of M0. Figure 3 b is the cross-sectional topography of M1. Figure 3 c is the cross-sectional topography of M2. Figure 3 d is the cross-sectional topography of M3. Figure 3 e is a cross-sectional topography diagram of M4.

[0089] Figure 4 The results shown are the water contact angle test results for five different porous nanofiltration membranes in Example 2 of this invention.

[0090] Figure 5 The results show the test results of the permeation flux and Congo red rejection rate of five different loose nanofiltration membranes in Example 3 of the present invention for Congo red solution.

[0091] Figure 6 The results show the test results of the permeation flux and NaCl rejection rate of five different loose nanofiltration membranes in Example 3 of the present invention for NaCl solution.

[0092] Figure 7 The results show the selective separation capabilities of five different loose nanofiltration membranes for Congo red and NaCl in a Congo red-NaCl mixed solution, as presented in Example 3 of this invention.

[0093] Figure 8 The results show the test results of the molecular weight cutoff of the MO and M3 membranes using PEGs of different molecular weights in Example 4 of the present invention.

[0094] Figure 9 The diagram shows the pore size distribution of the M0 and M3 membranes in Embodiment 4 of the present invention.

[0095] Figure 10 The results show the Zeta potential test results of the M0 and M3 membranes under different pH conditions in Example 4 of this invention.

[0096] Figure 11 The results shown are the test results of the permeation flux and dye retention performance of the M3 membrane for different dye molecule solutions with a concentration of 100 ppm in Example 5 of the present invention.

[0097] Figure 12 The results shown are the test results of the permeation flux and salt rejection performance of the M3 membrane in Example 5 of the present invention for different inorganic salt solutions with a concentration of 2000 ppm.

[0098] Figure 13 The results show the permeation flux and rejection rate of Congo red in the M3 membrane under different operating pressures in Example 6 of this invention.

[0099] Figure 14 a shows the test results of the M3 membrane in Example 6 of the present invention, in terms of the permeation flux to the Congo red solution and the rejection rate of Congo red within 1 to 14 hours.

[0100] Figure 14 b shows the test results of the M3 membrane in Example 6 of the present invention, in terms of the permeation flux to the Congo red-NaCl mixed solution and the rejection rate of Congo red and NaCl within 1 to 14 hours.

[0101] Figure 15 The results show the permeation flux and rejection rate of Congo red in the M3' membrane of Comparative Example 1 of this invention within 1 to 14 hours. Detailed Implementation

[0102] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.

[0103] It should be noted that the process equipment or apparatus not specifically mentioned in the following embodiments are all conventional equipment or apparatus in the art.

[0104] Furthermore, it should be understood that the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, does not preclude the presence of other method steps before or after the combined steps, unless otherwise stated. It should also be understood that the combined connection relationship between one or more devices / apparatus mentioned in this invention does not preclude the existence of other devices / apparatus before or after the combined devices / apparatus, or the insertion of other devices / apparatus between these explicitly mentioned devices / apparatus. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or defining the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.

[0105] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention; in the specification and claims of the present invention, unless otherwise expressly stated in the text, the singular forms "a", "an" and "this" include the plural forms.

[0106] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or equivalent to those described, apparatus, and materials in the embodiments of this invention may be used to implement the present invention.

[0107] Loose nanofiltration membranes are a new type of membrane material with pore sizes between nanofiltration (NF) and ultrafiltration (UF). They can be used at lower pressures and have high selectivity, with broad application prospects. They show significant advantages, especially in biomass and wastewater resource utilization, and are suitable for scenarios such as dye desalination, dyeing and printing wastewater treatment, and resource recycling.

[0108] Interfacial polymerization is a technique for rapidly polymerizing at the interface of two phases to form an ultrathin separation layer. The principle is as follows: two highly reactive monomers are dissolved in two immiscible solvents. When the two phases come into contact, a condensation reaction occurs at the interface to form a polymer film with a thickness of nanometers. This film is the separation functional layer.

[0109] To address the problems of low permeation flux and poor selectivity in salt dye separation of loose nanofiltration membranes in existing technologies, this application provides an interfacial polymerization method. This method uses a mixture of weakly and strongly reactive aqueous monomers as mixed monomers, which react with trimesoyl chloride (TMC). The membrane structure and crosslinking degree are controlled through the synergistic effect between the two types of monomers. Specifically, this application uses a polyacrylonitrile (PAN) nanofiber membrane as a substrate, on which a functional layer with separation capabilities is formed. The functional layer uses novel weakly reactive aqueous monomers piperazine-2-carboxylic acid (PIP-COOH) and polyethyleneimine (PEI) as aqueous two-phase monomers, and trimesoyl chloride (TMC) dissolved in an organic solvent as a crosslinking agent. PIP-COOH, PEI, and TMC undergo interfacial polymerization at the two-phase interface. During the reaction, PEI and TMC rapidly crosslink to form a dense membrane layer, effectively ensuring the retention performance of dye molecules; while PIP-COOH, as a small molecule with a fast diffusion rate, can effectively insert into the PEI-TMC crosslinking network, controlling the membrane pore size and significantly improving the membrane's permeation performance. The newly constructed nanofiltration membrane exhibits a significantly improved pure water flux compared to traditional PEI-based membranes, while also demonstrating excellent separation performance in a salt-dye binary system. Furthermore, the membrane maintains high dye retention capacity even when treating mixed dye wastewater.

[0110] The loose nanofiltration membrane prepared by this invention carries a negative charge and has a molecular weight cutoff of 539.36 Da, making it generally suitable for the separation of dyes with molecular weights greater than 550 Da, and particularly suitable for the separation of negatively charged dyes. This is because the negative charge on the membrane surface generates electrostatic repulsion with negatively charged dyes (such as reactive dyes and acid dyes), preventing the dye from passing through the membrane pores and achieving dye retention. The nanoscale pore size can physically block large molecular dyes while allowing small molecule salts to pass through. Small-sized salt ions (such as Na+) can also pass through. + Although Cl- is affected by weak electrostatics, it can still pass through the membrane pores due to concentration gradient (osmotic pressure) and high diffusivity, thus achieving the separation of dye and salt.

[0111] Example 1

[0112] The polyacrylonitrile used in this embodiment was purchased from DuPont, USA, and has a number average molecular weight of 150K.

[0113] The polyethyleneimine used in this embodiment was purchased from Shanghai Titan Co., Ltd., with a weight-average molecular weight of 600 Da.

[0114] Example 1 describes a method for preparing a loose nanofiltration membrane, comprising the following steps:

[0115] Step 1: Prepare PAN fiber base film by electrospinning.

[0116] 12g of polyacrylonitrile (PAN) powder was dissolved in 88g of N,N-dimethylformamide (DMF) and stirred at room temperature for 3 days to prepare a homogeneous PAN spinning solution. PAN fiber-based membranes were then prepared by electrospinning (spinning speed 16.7μL / min, voltage 20kV, collection distance 15cm, spinning temperature 25℃, spinning humidity 40%, spinning volume 5ml).

[0117] Step 2: Construction of the polyamide separation layer.

[0118] The PAN fiber-based membrane prepared in step one above was immersed in a mixed aqueous solution containing a certain concentration of polyethyleneimine (PEI) and piperazine-2-carboxylic acid (PIP-COOH). The mass concentrations of PEI and PIP-COOH in the mixed aqueous solution were controlled within the range of 0–0.05 wt%, and the immersion time was 2 min. After immersion, excess aqueous solution was removed from the membrane surface. Subsequently, the pretreated membrane was immersed in a 0.05 wt% trimethylbenzene chloride (TMC) / n-hexane organic phase for 1 min, resulting in an interfacial polymerization reaction to form a polyamide separation layer.

[0119] Step 3: Heat treatment crosslinking.

[0120] The membrane prepared above was placed in a 60°C oven and heated for 15 minutes to further promote the reaction between the aqueous monomer and TMC, thereby enhancing the crosslinking degree and stability of the membrane layer.

[0121] The prepared membranes were designated as M0, M1, M2, M3, and M4, respectively. M0 represents a mixed aqueous solution with a PEI concentration of 0.05 wt% and a PIP-COOH concentration of 0 wt%; M1 represents a mixed aqueous solution with a PEI concentration of 0.04 wt% and a PIP-COOH concentration of 0.01 wt%; M2 represents a mixed aqueous solution with a PEI concentration of 0.03 wt% and a PIP-COOH concentration of 0.02 wt%; M3 represents a mixed aqueous solution with a PEI concentration of 0.0225 wt% and a PIP-COOH concentration of 0.0275 wt%; and M4 represents a mixed aqueous solution with a PEI concentration of 0.02 wt% and a PIP-COOH concentration of 0.03 wt%.

[0122] Preparation process of the loose nanofiltration membrane of the present invention Figure 1 As shown.

[0123] Example 2

[0124] In this embodiment 2, scanning electron microscopy was used to observe the surface morphology and the thickness of the functional layer of the five different loose nanofiltration membranes prepared in embodiment 1 above, and the water contact angle of the membranes was tested.

[0125] The surface morphology results of the five loose nanofiltration membranes are as follows: Figure 2 As shown in a-2e. The results show that both PEI alone and PEI and PIP-COOH can react with TMC to form a complete functional layer on the surface of the PAN fiber-based membrane, proving the success of interfacial polymerization.

[0126] Cross-sectional views of five types of loose nanofiltration membranes are shown below. Figure 3 As shown in a-3e. The results show that as the concentration of PIP-COOH in the mixed aqueous solution increases, the thickness of the functional layer of the membrane gradually increases, from 28 nm (M0) to 44 nm (M4). This proves that the addition of PIP-COOH makes the membrane structure more porous, thus leading to an increase in membrane thickness. The porous structure is conducive to the transport of water molecules, thereby increasing the permeation flux.

[0127] The thickness of the loose nanofiltration membrane was tested using an Evit thickness gauge. The thickness was measured three times at different locations on the loose nanofiltration membrane and the average value was taken. The test results showed that the thickness of the loose nanofiltration membrane prepared by this invention was between 40 μm and 50 μm.

[0128] Furthermore, the water contact angles of the five different loose nanofiltration membranes prepared above were tested. A contact angle meter was used to measure the surface water contact angle of the loose nanofiltration membranes to characterize the hydrophilicity of the membrane surface. The test results are as follows: Figure 4 As shown, the water contact angles are as follows: M0 is 62.7°, M1 is 49.4°, M2 is 54.7°, M3 is 65.6°, and M4 is 50.4°. This result demonstrates that the addition of PIP-COOH does not significantly affect the hydrophilicity of the membrane, and the resulting membrane is a hydrophilic membrane with low resistance to water molecule transport.

[0129] Example 3

[0130] Example 3 tests the retention performance of the five different loose nanofiltration membranes prepared above for single dyes, single salts, and selective separation effects on dye and salt systems.

[0131] (1) The flux and dye rejection performance of the membrane were tested in a dye solution with a concentration of 100 ppm. In this example, a 100 ppm aqueous solution of Congo red (CR) was used as the test solution, the temperature was set at 25°C, the flow rate was 0.5 L / min, and the operating pressure was 3 bar.

[0132] Test results are as follows Figure 5 As shown, the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane's dye rejection rate. The results indicate that with increasing PIP-COOH content, from M0 to M4, the membrane permeation flux to the feed solution gradually increases, from 19.4 L / m³ at M0. -2 h -1 bar -1 Increased to 73.9 L m -2 h -1 bar -1 The permeation flux of M0 is 19.4 L m. -2 h -1 bar -1 The permeation flux of M1 is 28.5 L / m³. -2 h -1 bar -1 The permeation flux of M2 is 30.6 L / m³. -2 h -1 bar -1 The permeation flux of M3 is 62.1 L / m³. -2 h - 1 bar -1 The permeation flux of M4 is 73.9 L / m³. -2 h -1 bar -1Meanwhile, the membrane rejection rate gradually decreased from 99.7% to 98.4%. Specifically, the rejection rates of M0, M1, and M2 were 99.7%, M3 was 99.5%, and M4 was 98.4%. This demonstrates that the addition of PIP-COOH indeed made the membrane structure more porous, significantly increasing the membrane permeation flux while maintaining a high rejection rate.

[0133] (2) The flux and salt rejection performance of the membrane were tested in a 2000 ppm salt solution. In this embodiment, a 2000 ppm NaCl aqueous solution was used as the test solution, the temperature was set at 25°C, the flow rate was 0.5 L / min, and the operating pressure was 3 bar.

[0134] Test results are as follows Figure 6 As shown, the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane salt rejection rate. The results show that compared to M0, the permeation flux of M1 to M4 all increased, while the salt rejection rate decreased. Furthermore, the salt rejection rates of M1 to M4 were all less than 20%, with the rejection rates of M0 to M4 being 33.9%, 18.6%, 18.1%, 1.6%, and 1.2%, respectively. This indicates that the addition of PIP-COOH makes the membrane more porous and provides better salt permeability. With increasing PIP-COOH content, the membrane permeation flux gradually increases, while the membrane rejection rate gradually decreases.

[0135] (3) The selective separation effect of the membrane on dye and salt was tested in a mixed solution of dye and salt with a dye concentration of 100 ppm and a salt concentration of 2000 ppm. In this embodiment, a mixed solution of CR and NaCl was used as the test solution, wherein the concentration of CR was 100 ppm, the concentration of NaCl was 2000 ppm, the temperature was set at 25°C, the feed flow rate was 0.5 L / min, and the operating pressure was 3 bar.

[0136] The selective separation capability of the membrane for CR and NaCl is calculated by introducing the separation factor (α) using the following formula.

[0137]

[0138] Among them, R NaCl R represents the membrane's rejection rate of NaCl. CR This represents the membrane's rejection rate of CR.

[0139] The results are as follows Figure 7 As shown, the separation factors of M1 and M2 are higher than those of M0, while the separation factor of M3 is slightly lower than that of M0. However, the separation factors of M1 to M3 are all above 190.

[0140] In summary, the dye rejection rates of M1 to M4 are all above 98%, and their permeation flux is higher than that of M0. Their salt rejection rates are all significantly lower than that of M0, which proves that the loose nanofiltration membrane prepared in this application can have a high dye rejection rate and a low salt rejection rate while ensuring high flux.

[0141] Example 4

[0142] In Example 4, the M0 and M3 membranes prepared above were selected, and their molecular weight cutoff, pore size distribution and zeta potential were tested.

[0143] First, the retention rates of M0 and M3 membranes for standard substances of different molecular weights were tested, and retention rate-molecular weight curves were plotted. The molecular weight at which the retention rate reached 90% was determined as the molecular weight cutoff. In this example, a neutral molecular weight polyethylene glycol (PEG) aqueous solution was used as the feed solution at a concentration of 1000 ppm, with molecular weights of 200 Da, 300 Da, 400 Da, 600 Da, 1000 Da, and 2000 Da. The test conditions were: temperature set at 25°C, feed flow rate at 0.5 L / min, and operating pressure at 3 bar. The retention rates of the membranes for PEG of different molecular weights were tested, and retention rate-molecular weight curves were plotted. Specific results are as follows: Figure 8 As shown, the molecular weight cutoff of the M0 membrane (PEI / TMC) is 313 Da, and the molecular weight cutoff of the M3 membrane (PEI-PIP-COOH / TMC) is 539 Da.

[0144] Furthermore, using aqueous solutions of PEG with different molecular weights as feed solutions, the average effective pore radius (μm) of the membrane was measured by solute transfer method. p ) and geometric standard deviation (σ p Based on the retention rate and molecular weight, a logarithmic global distribution model was fitted using nonlinear regression to obtain the average effective pore radius (μ). p ) and geometric standard deviation (σ p The pore size distribution curves of the M0 and M3 membranes were obtained as follows: Figure 9 As shown in the figure, the horizontal axis represents the pore size of the membrane, and the vertical axis represents the probability density of the pore size. When PIP-COOH is added, the average effective pore radius of the membrane increases from 0.21 nm to 0.76 nm.

[0145] The above results collectively demonstrate that the addition of PIP-COOH successfully increases the membrane pore size and alters the membrane density.

[0146] Furthermore, a solid surface flow potential testing system was used to test the zeta potential of the membrane under different pH conditions. Specifically: the membrane was fixed in a test cell, and electrolyte solutions (solute was KCl) of different pH values ​​were added. The pH of the electrolyte solution was adjusted using HCl and NaOH, and the pH of the solution was measured using a pH meter. A pressure difference was applied, and the zeta potential was measured. The results are as follows: Figure 10 As shown, the membrane surface carries a negative charge, which is beneficial for improving the separation effect of negatively charged dyes.

[0147] Example 5

[0148] In Example 5, the M3 membrane prepared above was selected to test its ability to separate different dye molecules and different inorganic salts.

[0149] (1) Test the retention capacity of M3 for different dye molecules. Dye aqueous solutions with a concentration of 100 ppm were prepared, and six dye molecules were selected: methylene blue (MB, 319.8 Da), methyl orange (MO, 327.3 Da), rhodamine B (RB, 479.0 Da), acid fuchsin (AF, 585.5 Da), Congo red (CR, 696.6 Da), and direct red-80 (DR-80, 1373.1 Da). During the experiment, the feed liquid flow rate was maintained at 0.5 L / min and the operating pressure was 3 bar.

[0150] Test results are as follows Figure 11 As shown, the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane's dye rejection rate. The results indicate that when the relative molecular mass of the dye is less than 500 Da, the membrane's separation effect is poor, with a rejection rate of approximately 70-90%. When the relative molecular mass of the dye reaches 585.5 Da, the rejection rate increases to 98.0%, and further increases with increasing dye molecular weight. This shows that the membrane has a rejection rate of ≥98% for dyes with a relative molecular mass ≥585.5 Da. Furthermore, the membrane's permeation flux for AF is relatively low, possibly because the relative molecular mass of AF is close to the membrane's rejection molecular weight of 539 Da, causing it to clog the membrane pores and resulting in a lower flux compared to other dyes.

[0151] (2) Test the retention capacity of M3 for different inorganic salts. Prepare inorganic salt aqueous solutions with a concentration of 2000 ppm. Four inorganic salts were selected: NaCl, Na2SO4, MgCl2 and MgSO4. During the experiment, the feed flow rate was maintained at 0.5 L / min and the operating pressure was 3 bar.

[0152] Test results are as follows Figure 12As shown, the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane's rejection rate for inorganic salts. The results show that the membrane's rejection rate for all four salts is <30%, with rejection rates of 1.6% for NaCl, 21.4% for Na2SO4, 1.3% for MgCl2, and 15.2% for MgSO4. The highest rejection rate was observed for Na2SO4, possibly because the membrane surface carries a negative charge, resulting in a higher rejection rate for sulfate ions compared to chloride ions. 2+ The adsorption neutralizes the negative charge on the membrane surface, thereby reducing SO₂ levels. 4- The transmembrane transport resistance is high, resulting in the highest Na2SO4 rejection rate of this membrane.

[0153] In summary, the invention achieves relatively low rejection rates for the four inorganic salts, thus ensuring effective separation of salt stains.

[0154] Example 6

[0155] Example 6 examines the structural stability and long-term stability of the M3 membrane prepared above.

[0156] First, the structural stability of the membrane was investigated. A CR solution with a concentration of 100 ppm was prepared, and different operating pressures (1 bar, 2 bar, 3 bar, 4 bar, 5 bar) were used to test the effect of pressure changes on the membrane permeate flux and dye rejection rate.

[0157] Test results are as follows Figure 13 As shown, the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane's rejection rate for CR. The results indicate that with increasing pressure, the membrane permeation flux increases significantly, from 103.3 L / m³. -2 h -1 bar -1 (1 bar) increased to 245.4 L m -2 h -1 bar -1 (5 bar); and as the pressure increases, the membrane's dye rejection rate remains almost unchanged, consistently above 99.5%. This result demonstrates that the loose nanofiltration membrane prepared in this invention possesses excellent structural stability, and the membrane pore size does not deform within a pressure range of 1-5 bar.

[0158] Further investigation was conducted into the long-term stability of the membrane:

[0159] (1) The CR rejection rate and permeation flux of the membrane were tested using a single CR solution within 1–14 h. A CR solution with a concentration of 100 ppm was prepared, and the feed flow rate was 0.5 L / min and the operating pressure was 3 bar during the experiment.

[0160] Test results are as follows Figure 14 As shown in (a), the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane's rejection rate for CR. The results show that the membrane's rejection rate for CR remained essentially constant at over 99% during the 14-hour test, demonstrating that the membrane structure did not show any damage under prolonged testing. The permeation flux decreased slightly in the first 6 hours, possibly due to the compaction of the loose structure. As time gradually increased, the permeation flux remained essentially at 40 L / m². -2 h -1 bar -1 The above demonstrates that the membrane exhibits excellent structural stability under long-term testing.

[0161] (2) The CR / NaCl mixed solution was used to test the CR and NaCl rejection rates and permeation flux of the membrane within 1–14 h. A mixed solution with a CR concentration of 100 ppm and a NaCl concentration of 2000 ppm was prepared. The feed flow rate during the experiment was 0.5 L / min, and the operating pressure was 3 bar.

[0162] Test results are as follows Figure 14 As shown in (b), the left ordinate represents the membrane permeation flux, and the right ordinate represents the membrane's rejection rate for CR or NaCl. The results show that the membrane's rejection rate for CR remained essentially constant at around 99% during the 14-hour test, while its rejection rate for NaCl remained stable below 20%, demonstrating its excellent selective sieving ability for dyes in the treatment of mixed salt-dyed solutions.

[0163] In summary, the loose nanofiltration membrane prepared by this invention exhibits excellent structural stability during long-term operation, whether for pure dye systems or mixed systems of inorganic salts and dyes.

[0164] Comparative Example 1

[0165] Comparative Example 1 is a comparative example of M3 described above. In the preparation of M3, PIP was used instead of PIP-COOH, and the resulting membrane is denoted as M3'. Using the same CR solution and test conditions as in Example 6, the CR rejection rate and permeation flux of M3' were tested within 1–14 h; the results are as follows. Figure 15 As shown, the results indicate that the membrane can maintain a high CR rejection rate within 1–14 h, which is not significantly different from that of M3, but its permeation flux remains basically at 30 L / m². -2 h -1 bar -1 Left and right, with Figure 14 (a) In contrast, the membrane permeation flux decreased significantly. This is because the PIP after removing the carboxyl group has a weaker ability to regulate the interfacial polymerization reaction of PEI and TMC, and the resulting membrane is too dense, leading to a decrease in permeation flux.

[0166] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make various improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention. Any modifications, alterations, and equivalent changes made by those skilled in the art based on the above-disclosed technical content without departing from the spirit and scope of the present invention are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and evolutions made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A loose nanofiltration membrane, characterized in that, The loose nanofiltration membrane comprises a PAN fiber base membrane and a functional layer attached to the PAN fiber base membrane. The raw materials of the functional layer include a first aqueous phase raw material, a second aqueous phase raw material, and an organic phase raw material. The first aqueous phase raw material is selected from any one or two of polyethyleneimine and ethylenediamine. The second aqueous phase raw material is selected from any one or more of piperazine-2-carboxylic acid, 2,3-piperazine dicarboxylic acid, 1-methanesulfonylpiperazine, 2-cyanopiperazine, and N-acetylpiperazine. The organic phase raw material is selected from any one or more of trimesoyl chloride, terephthaloyl chloride, and isophthaloyl chloride.

2. The loose nanofiltration membrane according to claim 1, characterized in that, The number-average molecular weight of PAN used in the PAN fiber-based membrane is 100-200K. And / or, the weight-average molecular weight of the polyethyleneimine is 500 to 1000 Da; And / or, the mass ratio of the first aqueous phase raw material, the second aqueous phase raw material, and the organic phase raw material is 1:(0.2-5):(0.2-10).

3. The loose nanofiltration membrane according to claim 1, characterized in that, The functional layer is formed by sequentially immersing the PAN fiber base membrane in an aqueous raw material dispersion and an organic raw material dispersion; the aqueous raw material dispersion includes the following characteristics: a) The concentration of the first aqueous phase feedstock is 0.01 wt% to 0.1 wt%; b) The concentration of the second aqueous phase feedstock is 0.01 wt% to 0.1 wt%; c) The solvent in the aqueous raw material dispersion is water; The organic phase raw material dispersion includes the following characteristics: a) The concentration of the organic phase raw material is 0.01 wt% to 0.1 wt%; b) The solvent in the organic phase raw material dispersion is selected from any one or two of n-hexane and cyclohexane.

4. The loose nanofiltration membrane according to claim 1, characterized in that, The thickness of the loose nanofiltration membrane is 40–50 μm; And / or, the thickness of the functional layer in the loose nanofiltration membrane is 30–50 nm; And / or, the water contact angle of the loose nanofiltration membrane is ≤70°; And / or, the pore size of the loose nanofiltration membrane is 0.2–2 nm; And / or, the average effective pore radius (μm) of the loose nanofiltration membrane p The wavelength is 0.7–0.8 nm. And / or, the geometric standard deviation (σ) of the pore size of the loose nanofiltration membrane. p <1.5; And / or, the zeta potential of the loose nanofiltration membrane in a KCl electrolyte solution with a pH of 3 to 10 is <0.

5. The loose nanofiltration membrane according to claim 1, characterized in that, The porous nanofiltration membrane exhibits a rejection rate of >98% for Congo red in a 100 ppm aqueous solution, with a solution flux ≥28 L / m³. -2 h -1 bar -1 ; And / or, the loose nanofiltration membrane has a NaCl rejection rate of <20% and a solution flux of >35 L / m³ in a 2000 ppm NaCl aqueous solution. -2 h -1 bar -1 ; And / or, the loose nanofiltration membrane has a salt staining separation factor >60 in a mixed aqueous solution of Congo red 100 ppm and NaCl 2000 ppm; And / or, the loose nanofiltration membrane has a molecular weight cutoff of 530–545 Da.

6. A method for preparing a loose nanofiltration membrane as described in any one of claims 1 to 5, characterized in that, The method includes: sequentially immersing a PAN fiber base membrane in an aqueous phase containing aqueous raw materials and an organic phase containing organic raw materials, and then crosslinking it by heating to prepare the loose nanofiltration membrane.

7. The preparation method according to claim 6, characterized in that, PAN fiber-based membranes were prepared by electrospinning. The electrospinning solution used DMF and / or acetone as solvents, and the concentration of PAN in the electrospinning solution was 10-20 wt%. Preferably, the electrospinning parameters are any one or more of the following: spinning amount of 3-8 mL, pushing speed of 10-20 μL / min, voltage of 15-25 kV, collection distance of 10-20 cm, spinning temperature of 20-30 °C, and spinning humidity of 30%-50%.

8. The preparation method according to claim 6, characterized in that, The PAN fiber base is soaked in an aqueous phase containing aqueous raw materials for 1 to 10 minutes. And / or, the PAN fiber base is soaked in an organic phase containing organic phase raw materials for 1 to 10 minutes; And / or, the temperature for the heating crosslinking is 60–80°C; And / or, the heating crosslinking time is 10 to 20 minutes.

9. The use of a loose nanofiltration membrane as described in any one of claims 1 to 5 for removing hydrophilic macromolecules with a molecular weight ≥ 550 Da from aqueous solutions.

10. Use of a loose nanofiltration membrane as described in any one of claims 1 to 5 for removing hydrophilic dyes with a molecular weight ≥ 550 Da from an aqueous solution.